2008
DOI: 10.1007/s11258-008-9462-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of artificial defoliation techniques using canola (Brassica napus)

Abstract: We conducted two experiments that investigated how the method and location of artificial defoliation influenced growth, reproduction, and allocation in canola, Brassica napus. In one experiment, 0%, 25%, or 50% of leaf area was removed by cutting circular holes at three possible locations: concentrated at either the base of leaves or at their tips, or dispersed throughout leaf blades. Plants fully compensated for such damage; reproduction and allocation were unaffected by either defoliation intensity or wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(63 reference statements)
0
11
1
Order By: Relevance
“…This distinction may explain a lack of fecundity consequences from herbivory in some other potted plant studies of wild relatives of cole crops, which have shown strong compensation in terms of seed set ( [53,54] for R. raphanistrum and [55] for B. nigra). An average plant cover of ∼90% grasses and forbs already established or building in the first months after germination of our test plants contrasted starkly with less crowded growing conditions in a majority of previous studies testing for tolerance to herbivory in pots (e.g., [20,[56][57][58][59]) or weeded field sites (e.g., [60,61]). These studies, and the small scale field study of Strauss et al [62] on wild radish are not inconsistent with our fitness results if plants in these protected conditions rarely suffered mortality or if seed output was calculated only from plants that lived to reproduce (rather than including zero seed production for plants that died as juveniles).…”
Section: Herbivory and Plant Fitnesscontrasting
confidence: 59%
See 1 more Smart Citation
“…This distinction may explain a lack of fecundity consequences from herbivory in some other potted plant studies of wild relatives of cole crops, which have shown strong compensation in terms of seed set ( [53,54] for R. raphanistrum and [55] for B. nigra). An average plant cover of ∼90% grasses and forbs already established or building in the first months after germination of our test plants contrasted starkly with less crowded growing conditions in a majority of previous studies testing for tolerance to herbivory in pots (e.g., [20,[56][57][58][59]) or weeded field sites (e.g., [60,61]). These studies, and the small scale field study of Strauss et al [62] on wild radish are not inconsistent with our fitness results if plants in these protected conditions rarely suffered mortality or if seed output was calculated only from plants that lived to reproduce (rather than including zero seed production for plants that died as juveniles).…”
Section: Herbivory and Plant Fitnesscontrasting
confidence: 59%
“…Wild relatives of transformed plants that obtain IR traits through gene flow and introgression may be released from the pressure exerted by susceptible herbivores [6][7][8][9][10][11][12][13][14]. However, scant knowledge about the ecological factors that regulate the abundance, competitive ability, or geographic range of weeds limits our ability to predict whether novel plant defenses are likely to increase the weediness of wild crop relatives [14] or even whether herbivory has a negative or positive effect on plant growth and fitness [15][16][17][18][19][20]. Surprisingly, few tests have been conducted on the effects of herbivory on the spread of invasive plants [21,22] or to quantify the effects of herbivory on plant vital rates [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our study allows yield prediction for multiple defoliation scenarios with particular application to hail damage and natural events, such as frost or unmanaged animal grazing, where a single defoliation event leads to loss of contiguous patches of leaf area. A previous study showed that canola plants fully recovered when holes were scattered over the leaf surface, while they lost yield when contiguous patches of equivalent leaf area were removed (Susko and Superfisky, 2009). Similarly, studies in which authors removed leaf area gradually as plants grew reported smaller yield losses than those reported here (Susko and Superfisky, 2009;Kirkegaard et al, 2012a).…”
Section: Source Of Variationmentioning
confidence: 55%
“…A previous study showed that canola plants fully recovered when holes were scattered over the leaf surface, while they lost yield when contiguous patches of equivalent leaf area were removed (Susko and Superfisky, 2009). Similarly, studies in which authors removed leaf area gradually as plants grew reported smaller yield losses than those reported here (Susko and Superfisky, 2009;Kirkegaard et al, 2012a). This information suggests that one should be cautious in applying this information to insect defoliators such as diamondback moth [Plutella xylostella (L.)] or flea beetles (Phyllotreta spp.)…”
Section: Source Of Variationmentioning
confidence: 98%
See 1 more Smart Citation